2020
DOI: 10.1111/1440-1681.13307
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA XIST promotes chemoresistance of breast cancer cells to doxorubicin by sponging miR‐200c‐3p to upregulate ANLN

Abstract: The resistance of breast cancer cells to drugs is a major obstacle to effective cancer chemotherapy. Here, we study the function mechanisms of long non‐coding RNA XIST in chemoresistance of breast cancer to doxorubicin. We examined the 50% inhibitive concentration of doxorubicin to MDA‐MB‐231 and MDA‐MB‐231/ADM cells, showing that the doxorubicin resistance of MDA‐MB‐231/ADM cells was much higher than MDA‐MB‐231 cells. The gene or protein expression of XIST and ANLN were also higher in MDA‐MB‐231/ADM cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Interestingly, miR-940 also regulates the in ammatory response in osteoarthritis (OA) (15) and spinal cord injury (16). lncRNA XIST enhances ANLN by up-regulating miR-200c-3p, promotes the chemical resistance of breast cancer cells to doxorubicin and provides a potential new therapeutic target for the breast (17). The exosomes rich in miR-2277-30p tend to have a high abundance of β4 and lead to a cancer promoting effect (18).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-940 also regulates the in ammatory response in osteoarthritis (OA) (15) and spinal cord injury (16). lncRNA XIST enhances ANLN by up-regulating miR-200c-3p, promotes the chemical resistance of breast cancer cells to doxorubicin and provides a potential new therapeutic target for the breast (17). The exosomes rich in miR-2277-30p tend to have a high abundance of β4 and lead to a cancer promoting effect (18).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can act as a ceRNA by sponging miRNA to reduce the regulatory effect of miRNA on its target [22,25]. To explore the regulatory mechanisms by which lncRNA MPNCR affects the proliferation of BMECs, we determined its subcellular localization using the PCR method.…”
Section: Lncrna Mpncr Acts As a Molecular Sponge For Mir-31mentioning
confidence: 99%
“…Long non-coding RNA XIST promotes chemoresistance of breast cancer cells to doxorubicin by sponging miR-200c-3p to upregulate the expression of ANLN, which is a downstream target gene of miR-200c-3p [25]. LncRNA-PNUTS serves as a competitive sponge for miR-205 during EMT, and its expression correlates with ZEB mRNA level [26].…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, bioinformatics analysis demonstrated that ANLN might be a candidate biomarker for evaluation of survival [7]. Meanwhile, ANLN awarded chemotherapy resistance ability to breast cancer and reduced the effectiveness of Doxorubicin or Anthracycline [8,9]. Based on large experiments, ANLN promotes the progression in cancer and might be a novel target in cancer therapy [10].…”
Section: Introductionmentioning
confidence: 99%